Role and limitations of the geometric mean method regarding head rotation in salivary gland scintigraphy: a phantom study. (9th July 2020) - Chen, I-Feng; Lin, Li-Fan; Lin, Chun-Long; Chung, Tzu-Jou; Tseng, Ta-Wei; Chiu, Chuang-Hsin
Abstract: To investigate the possible influence of head rotation on the results of salivary gland scintigraphy, a phantom study was designed to simulate clinical salivary gland scintigraphy. The quantitative accuracy of regional activity counts was compared for two data acquisition methods involving head rotation: (i) an anterior planar projection-only (ANT) method and (ii) a geometric mean (GM) method using both the anterior and posterior planar projections. The roles and limitations of the GM and ANT methods when used at different head rotation angles were examined. Parallel planar projections of a head phantom with four salivary gland simulators, containing 3.7 MBq 99m Tc-sodium pertechnetate, at various rotational settings were acquired using a dual-head gamma camera. The difference between the standard activity counts (no phantom rotation) and the activity counts affected by the phantom rotation was calculated and defined as the rotational bias that decreased the accuracy of activity quantification. For small-angle rotation (≤10°), use of the GM method decreased the bias for all salivary gland simulators. In contrast, the bias of large-angle rotation (>10°) between four salivary gland simulators became conspicuous and complex in both methods. This bias may reflect different attenuation effects caused by displacement of the structures. Our data suggest that the GM method can be used when the head rotation angle is small (≤10°); however, when the head rotation angle is >10°, the non-negligible influence of head rotation should be considered during image acquisition.